2011
DOI: 10.1093/alcalc/agq099
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Gambling in Treatment-Seeking Alcoholics: A National Survey in France

Abstract: -Aims: To estimate the prevalence of pathological gambling ( pG) in people addicted to alcohol and drugs, particularly those with alcohol use disorders (AUDs), including new forms of gambling such as video and on-line games; and to update the sociodemographic profile of people suffering from both AUD and pG. Method: A cross-sectional survey was conducted in 1 week of 2009 in 55 French addiction treatment centres, including all consecutive patients attending that centre, using an anonymous questionnaire which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Demographics variables known in previous research ( Johansson et al, 2009 , Marsh and Dale, 2005 , Matzger et al, 2004 , Nalpas et al, 2011 , Swendsen et al, 2009 ) to predict or to be likely to predict GD and AUD, and admitted for in the Monitoring project, were chosen as confounding variables in the analyses (gender, age, education, residence size, marital status, occupational status, country of origin and smoking). Even though smoking is not a demographic variable it is a behavior that is highly comorbid with both problem gambling and excessive drinking ( Harrison et al, 2008 , McGrath and Barrett, 2009 ) and was therefore chosen to be included as a potential confounder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographics variables known in previous research ( Johansson et al, 2009 , Marsh and Dale, 2005 , Matzger et al, 2004 , Nalpas et al, 2011 , Swendsen et al, 2009 ) to predict or to be likely to predict GD and AUD, and admitted for in the Monitoring project, were chosen as confounding variables in the analyses (gender, age, education, residence size, marital status, occupational status, country of origin and smoking). Even though smoking is not a demographic variable it is a behavior that is highly comorbid with both problem gambling and excessive drinking ( Harrison et al, 2008 , McGrath and Barrett, 2009 ) and was therefore chosen to be included as a potential confounder.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of other psychiatric disorders, such as depression, anxiety and personality disorders, has shown to be significantly higher in individuals with both GD and AUD, than in individuals with GD only ( Abdollahnejad, Delfabbro, & Denson, 2014 ). In addition, demographic factors such as age, gender, marital status, residential size, ethnicity, education, income and employment are associated with both gambling and drinking ( Johansson et al, 2009 , Marsh and Dale, 2005 , Matzger et al, 2004 , Nalpas et al, 2011 , Swendsen et al, 2009 ). However, there seem to be gender differences and some studies have not confirmed an association between problematic gambling and drinking among females ( Griffiths et al, 2010 , Huang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gambling and substance use disorders share similar presentations of some symptoms (Petry 2006; Toce-Gerstein et al 2003), and the two disorders consistently demonstrate high rates of comorbidity in epidemiological as well as clinical samples (Kessler et al 2008; Lorains et al 2011; Nalpas et al 2011; Petry et al 2005b). Data are emerging that gambling and substance use disorders have common underlying genetic vulnerabilities (Black et al 2006; Blanco et al 2012; Slutske et al 2000;), and both are associated with similar biological markers and cognitive deficits (Blanco et al 2012; Potenza et al 2003; Reuter et al 2005).…”
Section: Changes To the Name And Placement Of Pathological Gambling Imentioning
confidence: 99%
“…Given the high rates of comorbidity between gambling and substance use disorders (Kessler et al 2008; Lorains et al 2011; Nalpas et al 2011; Petry et al 2005b), greater screening for gambling problems in these settings should enhance diagnostic efforts and increase the likelihood that individuals with gambling disorder are offered treatment. Given that brief interventions can be efficacious in reducing gambling problems (Hodgins et al 2001, 2009; Petry et al 2008, 2009), greater screening and treatment may reduce the public health burden of gambling disorders.…”
Section: How the Changes May Impact Diagnosis And Treatmentmentioning
confidence: 99%
“…The prevalence of problem gambling is higher among substance abusers than among the general population (Lorains, Cowlishaw, & Thomas, 2011;Nalpas et al, 2011;Petry, Stinson, & Grant, 2005;Potenza, Steinberg, & Wu, 2005). Studies of persons diagnosed with substance abuse in residential treatment facilities have found problem gambling to range from 10.5% to 14.9% (Toneatto & Brennan, 2002;Toneatto, Ferguson, & Brennan, 2003).…”
Section: Correlates Of Problem Gamblingmentioning
confidence: 99%